Emergent Forms: Origins and Early Development of Human Action and Perception - Goldfield, Eugene C. (New York Oxford University Press, 1995)
While it is often assumed that behavioral development must be based upon both physical law and the biological principles of morphogenesis and selection, forging a link between these phenomena has remained an elusive goal. Now in Emergent Forms, psychologist Eugene C. Goldfield offers an exciting new theoretical framework--based, in part, on the concept of self-organization--that promises to aid researchers in their quest to discover the underlying origins and processes of behavioral development. Addressing the question of how familiar human functional acts--such as eating, walking, manipulating objects, and smiling--emerge during infancy, Goldfield proposes that during perceptually guided spontaneous activity a variety of biodynamic devices for doing different kinds of work are assembled and adapted to specific tasks. Throughout, the theory is examined in the context of development, and extended to atypical development and other domains, such as cognition and language. The author also addresses many long-standing issues in behavioral development, including the apparent disappearance of so-called primitive behaviors, the emergence of new skills, and the role of the caregiver in skill acquisition. The author concludes his work by discussing how the implications of this research can be applied to understanding abnormal development in children who are motor impaired. Interdisciplinary in scope and accessible to a broad range of readers, Emergent Forms will fascinate students and researchers of ecological, developmental, evolutionary, and cognitive psychology.